Effect of differing doses of inhaled budesonide on markers of airway inflammation in patients with mild asthma. Issue 2 (1st February 1999) - Jatakanon, Anon; Kharitonov, Sergei; Lim, Sam; Barnes, Peter J
Abstract : BACKGROUND: It is desirable to prescribe the minimal effective dose of inhaled steroids to control asthma. To ensure that inflammation is suppressed whilst using the lowest possible dose, a sensitive and specific method for assessing airway inflammation is needed. METHODS: The usefulness of exhaled nitric oxide (NO), sputum eosinophils, and methacholine airway responsiveness (PC20 ) for monitoring airway inflammatory changes following four weeks of treatment with an inhaled corticosteroid (budesonide via Turbohaler) were compared. Mild stable steroid naive asthmatic subjects were randomised into two double blind, placebo controlled studies. The first was a parallel group study involving three groups receiving either 100 μg/day budesonide (n = 8), 400 μg/day budesonide (n = 7), or a matched placebo (n = 6). The second was a crossover study involving 10 subjects randomised to receive 1600 μg budesonide or placebo. The groups were matched with respect to age, PC20, baseline FEV1 (% predicted), exhaled NO, and sputum eosinophilia. RESULTS: There were significant improvements in FEV1 following 400 μg and 1600 μg budesonide (11.3% and 6.5%, respectively, p<0.05). This was accompanied by significant reductions in eosinophil numbers in induced sputum (0.7 and 0.9 fold, p<0.05). However, levels of exhaled NO were reduced following each budesonide dose while PC20 was improved only with 1600 μg budesonide. These results suggest that exhaled NO and PC20 may not reflect the control of airway inflammation as accurately as the number of eosinophils in sputum. There were dose dependent changes in exhaled NO, sputum eosinophils, and PC20 to inhaled budesonide but a plateau response of exhaled NO was found at a dose of 400 μg daily. CONCLUSION: Monitoring the number of eosinophils in induced sputum may be the most accurate guide to establish the minimum dose of inhaled steroids needed to control inflammation. This, however, requires further studies involving a larger number of patients.